SPECIALIZED MOBILE GAMES IN PRACTICAL EXERCISES ON THE NATIONAL FIGHT OF KURASH - Xujayorova Orzugul Berdiyor qizi; Suvonov Obidjon Shukurullayevich; Maksimov Furkat Sulaymanovich; Khusainov ShamshidinYalgashevich (Scholar Express Journals, 2021)
Outdoor play is an effective method of physical education. This paper discusses the use of specialized outdoor games in national kurash wrestling classes
Keywords: Specialized outdoor games; sambo wrestling; classes; teacher